2008
DOI: 10.1097/brs.0b013e3181734a8a
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Low Back Pain Behavior Are Reflected in the Cerebral Response to Tactile Stimulation of the Lower Back

Abstract: Successful adjustment to cLBP is associated with a patient's ability to effectively engage a sensory modulation system. In patients in whom such activation does not occur, subjective lack of control maypredispose to altered affective and behavioral responses with poor adjustment to pain. Pain experience may be furthermodified by reorganization of somatosensory cortex, contributing to maintenance of the chronic pain state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 24 publications
2
81
2
2
Order By: Relevance
“…Background and Aims: Evidence indicates that chronic non-specific low back pain (CNSLBP) is associated with alteration in the brain's cortical representation of the back, resulting in body perception disturbance and contributing to the condition [1,2]. This study investigated perception via 'cortical' sensory tests, in this case two-point discrimination and graphaesthesia-whose results partly depend on the integrity of cortical representation [2].…”
Section: Tactile Thresholds Are Preserved Yet Complex Sensory Functiomentioning
confidence: 99%
“…Background and Aims: Evidence indicates that chronic non-specific low back pain (CNSLBP) is associated with alteration in the brain's cortical representation of the back, resulting in body perception disturbance and contributing to the condition [1,2]. This study investigated perception via 'cortical' sensory tests, in this case two-point discrimination and graphaesthesia-whose results partly depend on the integrity of cortical representation [2].…”
Section: Tactile Thresholds Are Preserved Yet Complex Sensory Functiomentioning
confidence: 99%
“…In addition to CLBP, cortical abnormalities occur in a wide variety of other chronic pain conditions, such as chronic headache, arthritis, and fibromyalgia (for review, see . Several studies have also indicated abnormal cortical function in people with CLBP (Giesecke et al, 2004;Baliki et al, 2008;Lloyd et al, 2008;Kobayashi et al, 2009;Tagliazucchi et al, 2010). Evidence from pain neuroimaging and transcranial magnetic stimulation studies has linked the DLPFC to pain modulation (Lorenz et al, 2003;Brighina et al, 2004;Fierro et al, 2010), placebo analgesia (Wager et al, 2004;Krummenacher et al, 2010), perceived control of pain (Pariente et al, 2005;Wiech et al, 2006), and pain catastrophizing (Seminowicz and Davis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is possible that WS are, at least in part, reflections of central sensitization, and the fMRI differences between the WS-H and WS-L groups are a manifestation of neurological changes associated with central sensitization. We have shown previously that there is some cortical re-organisation in response to differences in WS 35 . However, it is impossible to demonstrate 'cause and effect' with our current cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%